2020
DOI: 10.1021/jacs.0c04890
|View full text |Cite
|
Sign up to set email alerts
|

Charge Separation from an Intra-Moiety Intermediate State in the High-Performance PM6:Y6 Organic Photovoltaic Blend

Abstract: Bulk-heterojunction organic photovoltaic devices with nonfullerene acceptors (NFAs) exhibit efficient hole transfer with small interfacial energy offset, which results in power conversion efficiencies above 17% in single junction devices using the high-performance NFA of Y6. However, the underlying mechanism responsible for the hole transfer channel in the polymer/Y6 blends remains poorly understood. Herein, we report that the hole transfer channel of photocharge generation is mediated by an intra-moiety excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

36
427
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(464 citation statements)
references
References 70 publications
36
427
1
Order By: Relevance
“…To further confirm the efficient hole transfer from PF5-Y5 to PBDB-T in the all-PSCs despite their small HOMO offset of 0.14 eV, herein, the hole transfer dynamics of photo-induced carriers in the all-polymer blend film were probed using femtosecond-resolved transient absorption (TA) spectroscopy measurements under a nitrogen atmosphere. 48b, 53 According to the absorption of PBDB-T and PF5-Y5, the pump wavelength was selected as 800 nm. Moreover, according to the results of excitation intensity-dependent measurements of acceptor material pure films under a pump wavelength of 800 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm the efficient hole transfer from PF5-Y5 to PBDB-T in the all-PSCs despite their small HOMO offset of 0.14 eV, herein, the hole transfer dynamics of photo-induced carriers in the all-polymer blend film were probed using femtosecond-resolved transient absorption (TA) spectroscopy measurements under a nitrogen atmosphere. 48b, 53 According to the absorption of PBDB-T and PF5-Y5, the pump wavelength was selected as 800 nm. Moreover, according to the results of excitation intensity-dependent measurements of acceptor material pure films under a pump wavelength of 800 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3d–f ). We highlight that by tracking the growth of the transient EA signal we monitor the separation dynamics of excitons/CTEs into free charges, while other reports to date focused on measuring the charge transfer time across the D/A heterojunctions (i.e., dissociation of excitons into CTEs) in non-fullerene OSCs 29 , 40 42 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In semiconductors, many species, such as triplet states and charge states, could induce long-lived signal for the bleaching signal. Y6 is a small molecule, the primary excitation is LE states [ 33 ]; accordingly, the long-lived component could not be attributed to the decay of charge states. Considering the formation of triplet states via intersystem crossing is a common process in organic semiconductors, and the decay of triplet states is relatively long, we deduced that the long-lived component observed in the bleaching kinetics of Y6 solution was most likely due to the formation of the triplet state.…”
Section: Resultsmentioning
confidence: 99%
“…This increased intrinsic exciton lifetime in the film could be correlated with the formation of intermolecular excitons, because of the aggregation of the molecular backbone in the film. Very recently, Zhang et al found that the intramoiety excited states, which were similar to pseudo charge transfer state or intermolecular exciton, could be formed from local excitation on a time scale of ~0.2 ps in the Y6 film [ 33 ]. By comparing TA kinetics of Y6 in solution and film under the same excitation fluence.…”
Section: Resultsmentioning
confidence: 99%